Performance of turbo code in CDMA under AWGN channel - Babiker, Mohanad; Khalifa, Othman Omran; Hassan Abdalla Hashim, Aisha; Salami, Momoh Jimoh Emiyoka; Ahmed, Muhammed Zaharadeen (Science & Engineering Research Support soCiety, 2017)
Carrier Division Multiple Access is considered as an efficient technique in wireless communication due to its high possibility to serve an unlimited number of users. CDMA uses the same frequency concurrently with wireless communication. In this paper, the performance and evaluation of turbo code are duly presented followed by the examination of CDMA under AWGN channel was highlighted. The simulation estimated to achieve bit error rate of less than 10-2 frame size. To this end, the results of the simulation show that the Bit Error Rate is inversely proportional to the size of the frame and directly proportional the number of iteration in the decoder.